PERCEPTIONS OF STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM TOWARDS LMS IMPLEMENTATION DURING THE C0VID-19 PANDEMIC ERA - Hassan, Muhammad; Ginting, Donny Adiatmana; de Napoli, Fernando; Rosmen, Rosmen (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
ABSTRACT This study aims to determine the perception of iEnglish Language Education students at STKIP AL MAKSUM Langkat towards online learning via Moodle during th Covid-19 pandemic. The qualitative descriptive method was carried out by distributing questionnaires using Google Form to 45 students of English Education STKIP AL MAKSUM Langkat. The questionnaire was distributed after completing the learning process for 3 months. The results of this study state that the use of the Moodle application provides a new experience in online learning activities, students can easily operate several features of the Moodle application, the learning process expects students to use the Moodle application, the Moodle application is one of e-learnin ithat can support learning activities online, the use of the Moodle application because classmates agree to use the Moodle application, and students can use the Moodle application easily in carrying out online learning activities.